Electroacupuncture Inhibits NLRP3 Activation by Regulating CMPK2 After Spinal Cord Injury - Chen, Yi; Wu, Lei; Shi, Mengting; Zeng, Danyi; Hu, Rong; Wu, Xingying; Han, Shijun; He, Kelin; Xu, Haipeng; Shao, XiaoMei; Ma, Ruijie (Frontiers in Immunology, 2022)
Objectives This study aimed to evaluate the expression of cytosine monophosphate kinase 2 (CMPK2) and activation of the NLRP3 inflammasome in rats with spinal cord injury (SCI) and to characterize the effects of electroacupuncture on CMPK2-associated regulation of the NLRP3 inflammasome. Methods An SCI model was established in Sprague–Dawley (SD) rats. The expression levels of NLRP3 and CMPK2 were measured at different time points following induction of SCI. The rats were randomly divided into a sham group (Sham), a model group (Model), an electroacupuncture group (EA), an adeno-associated virus (AAV) CMPK2 group, and an AAV NC group. Electroacupuncture was performed at jiaji points on both sides of T9 and T11 for 20 min each day for 3 consecutive days. In the AAV CMPK2 and AAV NC groups, the viruses were injected into the T9 spinal cord via a microneedle using a microscope and a stereotactic syringe. The Basso–Beattie–Bresnahan (BBB) score was used to evaluate the motor function of rats in each group. Histopathological changes in spinal cord tissue were detected using H&E staining, and the expression levels of NLRP3, CMPK2, ASC, caspase-1, IL-18, and IL-1β were quantified using Western blotting (WB), immunofluorescence (IF), and RT-PCR. Results The expression levels of NLRP3 and CMPK2 in the spinal cords of the model group were significantly increased at day 1 compared with those in the sham group (p < 0.05). The expression levels of NLRP3 and CMPK2 decreased gradually over time and remained low at 14 days post-SCI. We successfully constructed AAV CMPK2 and showed that CMPK2 was significantly knocked down following 2 dilutions. Finally, treatment with EA or AAV CMPK2 resulted in significantly increased BBB scores compared to those in the model group and the AAV NC group (p < 0.05). The histomorphology of the spinal cord in the EA and AAV CMPK2 groups was significantly different than that in the model and AAV NC groups. WB, IF, and PCR analyses showed that the expression levels of CMPK2, NLRP3, ASC, caspase-1, IL-18, and IL-1β were significantly lower in the EA and AAV CMPK2 groups compared with those in the model and AAV NC groups (p < 0.05). Conclusion Our study showed that CMPK2 regulated NLRP3 expression in rats with SCI. Activation of NLRP3 is a critical mechanism of inflammasome activation and the inflammatory response following SCI. Electroacupuncture downregulated the expression of CMPK2 and inhibited activation of NLRP3, which could improve motor function in rats with SCI.